ZONING OF THE TERRITORY OF TRANSCARPATHIAN REGION ACCORDING TO THE TEMPERATURE PARAMETERS OF THE EARTH SURFACE AND OUTSIDE AIR - Kinash Р.; Huk Я. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The article presents the results of detailed studies of the temperature of the earth surface (snow) and the outside air for 6 research dates in 2013-2015 using the resources of remote sensing of the Earth and observation data at 9 weather stations of the Transcarpathian region. To calculate the temperatures of the earth surface (snow) at the heights of the horizons of topographic maps for 6 research dates in 2013-2015, the data of observations at 9 weather stations of Transcarpathian region and the temperature of the earth surface (snow) on 10 peaks of the Ukrainian Carpathians, obtained according to data from space images of the "Landsat 8" satellite. For a detailed calculation of the heating temperature of the earth surface (snow) at the heights of the horizons of the topographic maps in an interval of 200 m for the 8 dates of observations in 2013-2015, the directions between the initial stations (meteorological stations) with heights above the level of the Baltic Sea were applied. According to the results of the research conducted for the mountainous area in the territory of the Transcarpathian region, it was established that in sunny weather, regardless of the season, the lowest temperature of the earth surface was observed on the northern and northwestern slopes of the Carpathians. The most snow-covered massifs of the Ukrainian Carpathians are the highest mountain massifs of Chornohora and Svidovets. As a result of the conducted studies of the temperature parameters of the earth surface and external air for mountainous terrain in the territory of Transcarpathian region, a method was proposed to determine the temperature of the earth surface (snow) and external air at a given height of the territory of Transcarpathian region using a zoning map of temperature parameters. By using the developed zoning map of temperature parameters, it is possible to determine the temperature of the earth surface (snow) and the outside air at a given altitude for the territory of Transcarpathian region .